The Effect of Scout Extracurricular to the Integrity of the Students in Elementary School (Universitas Negeri Semarang, 2019)
The current issue for the Indonesian nation is the decline of the nation's character. This declining can be seen from the phenomena that occur in society such as students cheating during exams, some students do not report to the teachers when they found others' belonging, and during the scouting activities, some students cannot express their opinion in a discussion. Those facts indicate that Indonesian is still lack of integrity. This study aims to determine and analyze the influence of scout extracurricular activities on integrity. The ex post facto method was used with a data analysis technique using simple linear regression. The students at the elementary school level, the scout extracurricular coaches, the teachers, and the students' parents were the samples of this study. To obtain the data, questionnaires, interviews, and documentation were used. In order to make sure that the research data are valid, a questionnaire instrument test was carried out consisting of validity and reliability tests. The normality test and the linearity test were done first before testing the hypothesis. The results of this study revealed that scout extracurricular influences students' integrity. Hopefully, this research can be used as a basis for developing scout activities as a compulsory extracurricular in the 2013 curriculum.